Characteristics of the Application of Economic Law in Development in Indonesia - Chandra, Alex; Afriani, Linda (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2023)
Economic law develops as the background of the rapid growth and development of economic activity in almost all parts of the world. The presence of the main economic law aims to regulate and limit all economic activities for the implementation of economic activity and economic development are not always appropriate and ignore the rights and interests of the wider community. Law of increasing economic development, one example when entering the era of the free market. Objective application of the law in the Indonesian economy is to set the rule of law to be easy in terms of planning related to the economy and pemerataannya for economic policy towards a pro-people. Therefore, it is necessary that every topic of discussion was the economy or technology experts and legal experts are concerned, especially regarding the development of various forms of corporate law in the Indonesian economy to come, which, according to the Working Group for the Economy, Finance and Industry (Ekuin) seen as a problem that is still not enough to be touched by the Indonesian Corporate Law. Economics that must be addressed in the conceptual, systemic and professional, but also the field of economic law and must be studied in line with the policy direction of the economy.